Odpowiedź :
2(a-1)²-2(a+4)²-5(a-1)²= dla a=√2
2(a²-2a+1)-2(a²+8a+16)-5(a²-2a+1)=
=-3a²+6a-3-2a²-16a-32=
=-5a²-10a-35
-5(√2)²-10√2-35=-10-10√2-35=-10√2-45
2(a²-2a+1)-2(a²+8a+16)-5(a²-2a+1)=
=-3a²+6a-3-2a²-16a-32=
=-5a²-10a-35
-5(√2)²-10√2-35=-10-10√2-35=-10√2-45
2(√2-1)²-2(√2+4)²-5(√2-1)²= (√4-2)²-(√4+8)²-(√10-1)²= √16-√16+4-√16+√64+64-√100-√10+1=4-4+4-4+8+64-10-√10+1=63-√10
2(√2-1)²-2(√2+4)²-5(√2-1)²=2(√2²-2√2+1)-2(√2²-+8√2+16) -5(√2²--2√2+1)=3√2²+6√2-3-2√2²-16√2-32= -5(√2)²-10√2-35=-10-10√2-35=-10√2-45